Machinability investigation and sustainability analysis of high-pressure coolant assisted turning of the nickel-based superalloy Inconel 718. (January 2023) - Cica, Djordje; Kramar, Davorin
In recent years, issues related to eco-friendly machining have received more and more attention, leading to the development of new cooling/lubrication techniques. Herein, the paper investigates the effect of high-pressure coolant (HPC) supply on machining performance of Inconel 718 and compare with conventional flood cooling. Significant improvement in tool life, tool wear, tool-chip contact length, material removal volume, and cutting forces have been observed from the outcomes of HPC cooling condition. Moreover, in order to study the environmental impact of machining Inconel 718, a carbon emissions model was established and analyzed for high-pressure and flood cooling conditions, taking into account the carbon emissions from energy, material, cutting tool, and cooling/lubrication fluid. HPC assisted machining was revealed to be better as it makes possible a reduction in overall carbon emissions at higher cutting speeds. In addition, economic analysis for both cutting environments was also carried out. Significant improvement in reduction of the overall machining cost was observed under HPC conditions, especially at higher cutting speeds. In a nutshell, the findings revealed better performance of HPC assisted machining, with regard to machinability, environmental, and economic issues.